Moving towards Electronic Lecturer Evaluation System (E-LEva) in UiTM Pahang: a study across lecturers / Khairul Nizam Abd Halim and Razulaimi Razali - Abd Halim, Khairul Nizam; Razali, Razulaimi (UiTM Pahang & UPENA, 2008)
paper investigates the perception and attitudes of non-business major students in Universiti Teknologi MARA (UiTM) towards economics education and their relationship on students’ academic performance. One of the key performance indicators in the academic programme of the university is to achieve less than twenty percent failures in all subjects offered. A four-semester examination results revealed that students constantly obtained high failure rate in two economics introductory subjects. Using students taking these two economics courses as respondents, dimensions of attitudes towards economics education were identified through the use of an exploratory factor analysis. Four factors were extracted from a 26- item questionnaire identified as ‘Value’, ‘Difficulty’, ‘Cognitive’ and ‘Affective’. Cronbach’s Alpha for the four factors was acceptable. The findings suggested that there was no significant difference between male and female students on the four dimensions of attitude even though the achievement of female students’ was higher than males. Students who did not perform were found to have a more negative attitude on the four dimensions of attitude compared to those who performed. Regression of the final exam scores on the four latent variables obtained from the factor analysis revealed that subject difficulty and gender, taken together, were significantly associated with students’ achievement